UNIVERSITY IN «KNOWLEDGE SOCIETY» - Ragozin, N. P. (Anthropological Measurements of Philosophical Research, 2012)
The article studies peculiarities of development of modern university system of production and spreading of knowledge. There is given comparative analysis of historic types of university:prior to classical (Medieval Ages), classical ‘Gumboltd’s’ (New Age) and post classical university (XX – early XXI century). There is enlightened a tendency to bifurcation of post classicaluniversity into mass and elite university with a perspective of turning both of them into a capitalistic enterprise.